ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL DI INDONESIA - Dwi Umardani; Abraham Muchlish (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
ABSTRACTThis study aims to compare the financial performance of Islamic banks with conventional banks in Indonesia using financial ratios: CAR, NPL / NPF, ROA, ROE, LDR / FDR, REO / BOPO.The data used are the financial statements published by Bank Indonesia (BI), the annual reports released by banking companies listed in Indonesia Stock Exchange (IDX), the annual reports issued by companies of Islamic banking that are not listed in Indonesia Stock Exchange (IDX), and the Indonesian banking supervision reports contained in Bank Indonesia (BI) for the years 2005-2012.The analytical method used to compare the financial performance of Islamic banks with conventional banks is statistical test independent t-test.The fact shows that for each financial ratio of Islamic banks and conventional banks in Indonesia: CAR, ROA, ROE, LDR / FDR, and BOPO there are significant differences, while NPL / NPF there is not significant difference.Keywords: Financial performance, Islamic banks, conventional banks